1995
DOI: 10.1007/bf00174260
|View full text |Cite
|
Sign up to set email alerts
|

X-ray absorption spectroscopy of antiwear films on aluminum alloys generated from zinc dialkyldithiophosphate

Abstract: The boundary lubrication of A1 alloys 6061 (AI-6% Si) and A-390 (Al-18 wt% Si), by a sec-ZDDP (zinc dialkyldithiophosphate) oil blend was examined at 60 andl00~ The wear performance in the ZDDP blend was an improvement on base stock. At 100~ the ZDDP prevented scuffing, though no antiwear films could be detected due to the severe wear. At 60~ all samples showed initial scuffing followed by a more controlled wear given by an embedded antiwear film. P L-edge X-ray near-edge structure (XANES) spectroscopy using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 14 publications
2
21
0
Order By: Relevance
“…As a result, one would expect the formation and behavior of these films to be dictated by the chemical properties of the underlying substrate. The similarities between ZDDP AW films formed on a number of chemically distinct surfaces suggests otherwise [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 96%
“…As a result, one would expect the formation and behavior of these films to be dictated by the chemical properties of the underlying substrate. The similarities between ZDDP AW films formed on a number of chemically distinct surfaces suggests otherwise [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 96%
“…It is generally thought that the grains, after honing and etching of the surface, act like riders that bear the load of the conforming surfaces. Very little research has been performed on the lubrication of Al-Si alloys using ZDDP [36][37][38][39][40]. The findings already published contain conflicting conclusions.…”
Section: Introductionmentioning
confidence: 97%
“…In three of the four studies, the addition of the ZDDP additive to base oil had little or no effect in preventing wear. In two studies the authors used XANES [39,40] analysis to examine the wear scars for the presence of phosphorous decomposition products of ZDDP. The authors found that the ZDDP tribofilms, which form on the Al-alloys surfaces, are essentially identical to those that form on steel.…”
Section: Introductionmentioning
confidence: 99%
“…tribofilms, whether on iron [34], Al-Si alloys [14,35] or other coated surfaces [34]. In addition, several other studies [26,36] examined the effect of detergents and dispersants on the decomposition reactions and the synergy between the different oil additives.…”
Section: Introductionmentioning
confidence: 99%